Comparative study of the change in high-order aberrations after Nd: YAG laser capsulotomy in patients with different degrees of posterior capsule opacification (Research, Society and Development, 2020)
Objective: To evaluate the effect of posterior Nd: YAG laser capsulotomy on pseudophakic eyes in high-order, total and internal aberrations, in different degrees of posterior capsule opacification. Method: Experimental, prospective clinical study of a longitudinal cohort. The study included patients who had undergone cataract surgery (with spherical lens implantation) and had some degree of posterior capsule opacification (OCP). High-order aberrations were measured by the Nidek OPD III aberrometer before and 15 days after posterior Nd: YAG laser capsulotomy. The mean values ​​of total and internal aberrations - spherical, coma and trefoil - pre and post capsulotomy were compared in total and subdivided between degrees of OPC. Results: In all, 64 eyes were included. A statistically significant reduction was found in all total in-house aberrations after capsulotomy. For total aberrations, in grade I, there was a statistically significant reduction in trefoil aberrations, in grade II spherical, grade III spherical, coma and trefoil and grade IV coma and trefoil. For internal aberrations, grade I coma and trefoil, grade II coma, grade III and IV coma and trefoil. Conclusion: It has been shown that this procedure implies a statistically significant reduction in high order aberrations, both internal and total.